2020
DOI: 10.1359/jbmr.1998.13.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Bone Elasticity and Ultrasound Velocity Are Affected by Subtle Changes in the Organic Matrix

Abstract: The mechanical competence of bone can be studied through the measurement of the components of its material elasticity, a property which can vary both in magnitude and in dependence upon orientation (anisotropy). While it is known that the elasticity is largely determined by the mineral constituents of the bone matrix, it is nonetheless clear that it must be also dependent upon the remaining constituents of bone material. In this work, the influence of organic components on the elasticity is explored by alterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 53 publications
1
24
0
1
Order By: Relevance
“…In contrast, the anisotropy of SOS was preserved after decollagenization, indicating that the anisotropy in SOS is independent of collagen content. This result is consistent with experiments from other laboratories on cortical bone [5,6]. It is interesting to note that ultrasonic measurements performed on bovine Achilles tendon have shown that oriented collagen fibers can produce a large anisotropy in SOS [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the anisotropy of SOS was preserved after decollagenization, indicating that the anisotropy in SOS is independent of collagen content. This result is consistent with experiments from other laboratories on cortical bone [5,6]. It is interesting to note that ultrasonic measurements performed on bovine Achilles tendon have shown that oriented collagen fibers can produce a large anisotropy in SOS [16].…”
Section: Discussionsupporting
confidence: 92%
“…Both types of measurements correlate well with bone mineral density (BMD), and are sensitive to the anisotropic microstructure of bone. These measurements also may be sensitive to the protein matrix of bone [4][5][6][7]. Recent work by a few investigators has drawn attention to the possibility of developing new techniques based on ultrasonic backscatter [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques based on vibrational or wave propagation principles that have in vivo applications have been successful in detecting age-and disease-related changes in bone properties, 37,38 the effect of large structural defects on whole bone properties, 39,40 and in predicting the effect of microstructure, 41 bone mineral, 42 and organic components 43 on bone-tissue properties. The effect of mechanical damage on bone-tissue properties, however, has proven difficult to predict using similar means 44 despite their usefulness in detecting damage in engineering materials.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that QUS parameters are influenced not only by bone density as occurs for DXA, but also by bone structure and composition, so that they give additional information, compared with DXA, on some aspect regarding bone quality (7,8,10). In fact, some QUS parameters are able to detect collagen and organic matrix abnormalities in vitro (76,78) and in vivo (79), giving some information on the organic components of bone material. Anyway, there are too few data linking bone mineral status by DXA, pQCT, or QUS measure to fracture rate in children, and further studies in a large number of subjects are needed to investigate this crucial aspect.…”
Section: Qus Measurement In Patients With Bone and Mineral Disorders mentioning
confidence: 99%